DAMPAK KERJA SAMA INDONESIA DAN UNI EMIRAT ARAB MELALUI SHAREHOLDER AGREEMENT (SHA) DALAM MENINGKATKAN INFRASTRUKTUR PELABUHAN BELAWAN PERIODE I - Hasyim, Muhammad Umar; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
As an archipelagic country with a geostrategic position along global trade routes, Indonesia considers ports as vital infrastructure in supporting export and import activities. However, Belawan Port, one of the main ports in North Sumatra, continues to face various challenges, particularly in terms of infrastructure limitations and operational inefficiencies. This study aims to analyze the impact of the bilateral cooperation between Indonesia and the United Arab Emirates through the Shareholder Agreement (SHA) scheme on the improvement of Belawan Port infrastructure during Phase I. Employing a descriptive-qualitative approach, data were collected through literature review, official document analysis, and strategic policy evaluation. The findings indicate that the implementation of the SHA involving PT Pelabuhan Indonesia (Pelindo), the Indonesia Investment Authority (INA), and Dubai Port World (DP World) has accelerated port modernization, enhanced the attractiveness of foreign direct investment (FDI), and improved national logistics efficiency. Beyond economic dimensions, the cooperation also emphasizes sustainable development principles by integrating environmental considerations into both the planning and operational stages of the port. This cooperation model represents a strategic, adaptive, and visionary cross-border partnership that can serve as a reference for the development of maritime infrastructure based on international collaboration. Keywords: Shareholder Agreement, Port Infrastructure, Belawan Port, Foreign Investment, Sustainable Development.